2016
DOI: 10.1016/j.brainres.2016.02.051
|View full text |Cite
|
Sign up to set email alerts
|

The role of CHMP2BIntron5 in autophagy and frontotemporal dementia

Abstract: Charged multivesicular body protein 2B (CHMP2B) – a component of the endosomal complex required for transport-III (ESCRT-III) – is responsible for the vital membrane deformation functions in autophagy and endolysosomal trafficking. A dominant mutation in CHMP2B (CHMP2BIntron5) is associated with a subset of heritable frontotemporal dementia – frontotemporal dementia linked to chromosome 3 (FTD-3). ESCRT-III recruits Vps4, an AAA-ATPase that abscises the membrane during various cellular processes including auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 73 publications
(133 reference statements)
3
29
1
Order By: Relevance
“…The brains of FTD-3 patients with mutations in CHMP2B show many similar changes, including demyelination, gliosis and accumulation of ubiquitinated inclusions and p62, suggesting that loss of ESCRT-I function has similar effects to loss of ESCRT-III. It has been suggested that mutations in CHMP2B cause FTD-3 because they disrupt late endosome-lysosome fusion and autophagy (Lee and Gao, 2009;Urwin et al, 2010;Clayton et al, 2015;Krasniak and Ahmad, 2016), but our study shows that loss of RAB7, which mediates late endosome-to-lysosome trafficking and autophagosome-lysosome fusion events, does not cause vacuolation.…”
Section: Discussioncontrasting
confidence: 82%
“…The brains of FTD-3 patients with mutations in CHMP2B show many similar changes, including demyelination, gliosis and accumulation of ubiquitinated inclusions and p62, suggesting that loss of ESCRT-I function has similar effects to loss of ESCRT-III. It has been suggested that mutations in CHMP2B cause FTD-3 because they disrupt late endosome-lysosome fusion and autophagy (Lee and Gao, 2009;Urwin et al, 2010;Clayton et al, 2015;Krasniak and Ahmad, 2016), but our study shows that loss of RAB7, which mediates late endosome-to-lysosome trafficking and autophagosome-lysosome fusion events, does not cause vacuolation.…”
Section: Discussioncontrasting
confidence: 82%
“…The endosomal‐lysosmal pathway delivers transmembrane proteins to the lysosomal lumen for degradation . CHMP2B, a subunit of Endosomal Sorting Complex Required for Transport‐III (ESCRT‐III), mediates the endosomal sorting of ubiquitinated transmembrane proteins into the multivesicular bodies (MVBs) for transport to lysosomes . Consequently, CHMP2B and other ESCRT subunits play a critical role in the regulation of multiple cell surface receptors and their signaling cascades .…”
Section: Introductionmentioning
confidence: 99%
“…The Danish version of FTD3 has spread in a large family and is caused by a single nucleotide mutation translated into shortened and altered C-terminus of the CHMP2B protein (Skibinski et al, 2005;Urwin et al, 2010;Zhang et al, 2017). CHMP2B is an important part of the endosomal sorting complex required for transport-III (ESCRT-III) and for a proper function of the intracellular endolysosomal pathway (Krasniak and Ahmad, 2016;Urwin et al, 2010;van der Zee et al, 2008). The mutation results in truncated CHMP2B unable to mediate the endosomal-lysosomal fusion and processing.…”
Section: Human Ipscs For Modelling Neurodegenerationmentioning
confidence: 99%